PENGARUH KESEJAHTERAN PETANI TERHADAP KEMISKINAN DI PERDESAAN - Rahmawati, Nurul (Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This study aims to answer the question, does increasing farmers’ welfare have a significant impact on reducing poverty in rural areas? The results of the analysis of FTT data, percen-tage of rural poverty, and rural Gini Ratio in 2014-2017 using the fixed effect panel data re-gression with pooled EGLS method (Cross-section weights) show that farmers’ welfare has a significant impact in reducing poverty in rural areas. The reduction will be more effective if the increase in farmers’ welfare is accompanied by equitable distribution of income in ru-ral areas. Keywords: Panel, Unequality, Farmers’ Terms of Trade, Poverty